Long-Term Outcomes of Paraplegics in a Resource-Limited Society: Are We Doing Enough? - Tanki, Humam N.; Khursheed, Nayil; Khan, Abdul Q.; Ganie, Majid A.; Ramzan, Altaf U.; Tanki, Farah N.; Wani, Abrar A. (Indian Journal of Neurotrauma, 2015)
Cases of paraplegia form a considerable proportion of patient population visiting neurosurgical and neurologic units. Paraplegia not only alters the physical condition of the patient but also his/her mental, psychological, and social well-being. We collected data of 30 patients with paraplegia admitted during a period of 4 years who were followed then for a minimum period of 1 year. Those patients were evaluated for their neurologic improvement and complications usually associated with paraplegia. We found that patients with preserved sensations have better outcome and should be aggressively treated by surgery; whereas in patients who have no motor and sensory function at the time of injury, the decision regarding surgery should be guarded. We also derived that most common complications on follow-up include pressure sores, bladder dysfunction, and deep venous thrombosis, and evaluating them for depression and anxiety is mostly overlooked. We stress that the need of the hour in a resource-limited society such as ours is an intensely committed psychological rehabilitation in this group of patients.
Keywords: spinal cord injury; paraplegia; complications; psychological complications